From Face-to-Face to Face-to-Screen: Unveiling the Gaps in Student Confidence During Pandemic-Era Online Learning - Sitompul, Nurmida Catherine; Nurjati, Nunung (Universitas Pendidikan Ganesha, 2024)
The COVID-19 pandemic posed significant challenges to educational systems, particularly in reshaping students' learning patterns. This study aims to explore the motivation, emotions, and learning behaviors of students during the first year of the pandemic. A survey approach was employed, involving 383 undergraduate students enrolled in Elementary Teacher Education programs. Data were collected using a questionnaire that assessed self-efficacy, task value, boredom, frustration, elaboration strategies, metacognitive strategies, learning satisfaction, and students’ experiences with virtual face-to-face interactions. Descriptive analysis was conducted to identify patterns and relationships among variables. The results revealed that although students employed self-regulated learning strategies, they remained uncertain about their ability to independently comprehend material without lecturers' guidance. Virtual face-to-face sessions were frequently utilized as a scaffold to ask questions and confirm their understanding of the content. These findings indicate that emergency online learning during the pandemic did not meet the standards of an ideal online learning model. Students tended to maintain conventional learning patterns, exhibited high dependency on lecturers’ guidance, and lacked confidence in their independent learning outcomes. This study concludes that structured online learning approaches are necessary to foster students' learning autonomy. Such strategies should include enhanced self-regulation training to improve confidence and the overall quality of online education in the future.